A Study on the Current Status of Informal Learning Among College Normal Students (Journal of Global Humanities and Social Sciences, 2024)
Informal learning is a type of learning that contrasts with formal learning. It is characterized by autonomy, regulation, intentionality, flexibility, sociality, and diverse learning outcomes, free from time and space constraints. The current status of informal learning among normal students at local undergraduate teacher training colleges exhibits internal incompatibilities between a high level of awareness and low satisfaction with learning environments and support, a clear learning paths or methods and a strong desire for a platform to evaluate and certify learning outcomes. This study aims to stimulate learning motivation from an endogenous perspective and enhance the effectiveness of informal learning for normal students through appropriately guided external dimensions. The integration of the first, second, and third classrooms highlights the importance of practice, while the integration of explicit and implicit environments provides support and services. The concept of "micro-skills, micro-learning, micro-certification" through digital badges can be used to certify learning outcomes.